THE ATA SYSTEM: ITS ORIGIN, DEVELOPMENT AND SOCIO-ECONOMIC IMPACT ON THE SOCIETY OF MEDINA DURING THE ERAS OF THE RIGHTLY GUIDED CALIPHS (11-40AH/632-661AD) - Omer, Elkhalifa Mohamed (Journal of Al-Tamaddun, 2020)
There were limited economic resources during the time of the Prophet, and this in turn affected the way of life adopted by the Medinans. Consequently, economic problems remained one of the main difficulties facing the new community in Medina. As a result of the Futuh, during the time of the Rightly Guided Caliphs, the financial and economic institutions of the state were developed along with the resources of the Treasury. This in its turn led to the establishment of a payment system by the state which came to be known by the name of Ata (stipend). The major aim of this study is to shed light on some of the social and economic impacts of the Ata on the society of Medina during the time of the Rightly Guided Caliphs. The study concludes that establishment of the Ata produced an improvement of the economic situation of some Medinans who invested this amount of money in other economic activities, and this improvement in its turn affected the way they lived. Others failed to make profitable use of this regular income, while some abandoned their traditional sources of income, and became dependent on their stipends. The Ata had a negative effect on the involvement of the Medinans in trade, which started to decline as Quraysh's principal or traditional source of income.